2006
DOI: 10.1111/j.1600-0722.2006.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1α and tumor necrosis factor‐α expression during the early phases of orthodontic tooth movement in rats

Abstract: Remodelling of the periodontium after application of mechanical forces constitutes the basis of clinical orthodontics and various immunoregulatory molecules are involved in this process. The aim of this study was to investigate the expression of the cytokines interleukin-1alpha (IL-1alpha) and tumor necrosis factor-alpha (TNF-alpha) in dental tissues during the early phases of orthodontic tooth movement. Eightteen male Wistar rats were used. All maxillary right first molars were moved orthodontically, with a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
85
4
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 33 publications
4
85
4
5
Order By: Relevance
“…The role of cytokines in inflammation and bone remodeling has been extensively investigated during the last decade (5,7,22,26). Previous literature data indicated that TNF-α among other cytokines, can be closely associated with ethiopathogenesis of radicular cysts (6,16,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of cytokines in inflammation and bone remodeling has been extensively investigated during the last decade (5,7,22,26). Previous literature data indicated that TNF-α among other cytokines, can be closely associated with ethiopathogenesis of radicular cysts (6,16,19).…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α mostly triggers apoptosis and necrosis in sensitive tissues and has been linked to osteomyelitis and apical periodontitis, but it can also participate, in skeletal homeostasis, including osteoclastic formation, and bone resorption in the maxillofacial region. TNF-α, among other cytokines, can regulate fibroblast activity and collagen formation through modulation of collagenase activity (5,7,22,26). In addition, TNF-α can induce low dose proliferation of several cells and can be one of the reasons for tumour growth (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of intraoperative and postoperative complications revealed a high morbidity for laparotomy largely due to hemorrhage (11 cases, 9.4 %) and fever (11 cases, 9.4%); These complications were rare for mini-invasive routes: hemorrhage (1 case; 0.8%) and fever ( 1 case; 0.8%). In hysterectomy performed by mini-invasive routes inflammation is reduced, hemostasis is precise and particularly in laparoscopy due to amplification of pelvic structures, reducing by thus the inflammatory surface area and blood collections which breed pyrogenic substances (19,20) . As a result, an increase in the technical index makes it possible to minimize not only the morbidity and stay in hospital but also the global cost of management.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines, such as interleukins (IL)-1, -6, -8, and -11 and tumor necrosis factor-α (TNF-α), and prostaglandin (PG) E 2 released from periodontal ligament fibroblasts and alveolar bone osteoblasts can alter the normal process of bone remodeling, resulting in physiological bone resorption or bone formation [1][2][3][4][5][6] . The levels of these cytokines increase in the gingival crevicular fluid of teeth during orthodontic tooth movement.…”
Section: Introductionmentioning
confidence: 99%